1982
DOI: 10.1139/v82-203
|View full text |Cite
|
Sign up to set email alerts
|

Radical reactions in aqueous solution: use of the aci-anion of nitromethane as a spin trap

Abstract: The type of radical detected by esr when first-formed short-lived radicals are generated by photolytic, radiolytic, or flow techniques in the presence of nitromethane is shown to depend upon the nature and structure of the transient radical and on the pH. Thus electron-donating radicals may react with CH3NO2 itself under certain conditions to give rise to CH3NO2−• and the alkoxy nitroxides CH3N(OR)O•. At higher pH, a wide variety of radicals (X) react very readily with the aci-anion CH2:NO2− to give adducts XC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…According to the literature, the radical • CH 2 NO 2 can be generated in strong alkaline media by one‐electron oxidation of the nitromethane aci anion (Eqn (6)) . Therefore, we propose that under the given experimental conditions the nitromethane spin trap is oxidized by the short‐lived intermediates formed in the photodecomposition of selenadiazoloquinolones.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…According to the literature, the radical • CH 2 NO 2 can be generated in strong alkaline media by one‐electron oxidation of the nitromethane aci anion (Eqn (6)) . Therefore, we propose that under the given experimental conditions the nitromethane spin trap is oxidized by the short‐lived intermediates formed in the photodecomposition of selenadiazoloquinolones.…”
Section: Resultsmentioning
confidence: 86%
“…The spectrum in Fig. (d‐i) indicates the formation of radical anion CH 3 NO 2 • – , generated via electron transfer to nitromethane (Eqn (2)) . This points to an electron transfer from the photoactivated selenadiazoloquinolone (SeQ* in Eqn (3)) to the spin trap (Eqn (4)).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, to detect • OH, a small amount of DMSO was added. Upon reaction with • OH, it generates a methyl radical ( • CH 3 ), which can be efficiently spin-trapped by aci-nitromethane to produce a distinguishable EPR spectrum Therefore, for each series of experiments, we recorded spectra for otherwise identical samples both with and without DMSO. The spectra from solutions without DMSO were fit with a set of basis spectra for the • NO 2 and • NO adducts.…”
Section: Resultsmentioning
confidence: 99%
“…However, nitrones are not suitable for use at the very high pH levels associated with our solutions. Previous studies have shown that nitromethane and other nitroalkanes convert to the aci form above ∼0.5 M OH – where they can act as an effective spin trap in alkaline solutions. …”
Section: Methodsmentioning
confidence: 99%